Mechanical properties of epoxy-polyurethane polymer blends (Baghdad Science Journal, 2006)
Configured binary polymer blends of epoxy and Polyurethane was chosen varying proportions of these materials led to the production of homogeneous mixtures of Althermust Althermust and descent was poured polyurethane models required in the form of 4 mm thick plates